Workshop Pembuatan Video Pembelajaran Berbasis Kompetensi bagi Instruktur LPK di Kota Denpasar - Pramudito, Sabrina Jocelyne; Susanti, Luh Eka; Arun Suwi Arianty, A.A. Ayu; Astina, Made Arya; Eka Sudarmawan, I Wayan (Universitas Pahlawan Tuanku Tambusai, 2025)
Vocational Training Centre (Lembaga Pelatihan Kerja/LPK) are educational institutions that prepare skilled workers through a series of competency-based training programs. In Denpasar City, the delivery of engaging training materials that meet the needs of the younger, more visually-oriented generation still faces challenges, including the lack of innovative and relevant learning media, as well as limited technological skills among LPK instructors. This community service activity aims to improve the quality of learning through a workshop on creating competency-based learning videos for LPK instructors. The method involved presentations and hands-on practice in video production, including scriptwriting, video shooting, and basic editing. The results showed that each workshop participant successfully produced a simple learning video and gained a comprehensive understanding of the video-making process. Therefore, this workshop has significantly contributed to enhancing the quality of competency-based learning that is adaptive to the development of the digital era and the demands of the workforce.